Removal of malachite green from aqueous solution by using dried water hyacith (Eichhornia crassipes) - Ruwaida, Awang (2010)
This paper shows a detailed study to investigate the potential of water hyacinth as adsorbent, to remove Malachite Green from aqueous solution and to identify the optimum condition for the parameter involved. There were four parameters that have been studied in this paper, they were effect of adsorbent dosage, effect of initial concentration of dye, effect of pH and effect of time contact. It was found that the optimum dosage for the adsorbent at initial dye concentration of 60 mg/L was 0.6 g, the optimum pH was at 6 and the optimum time contact was at 60 minutes for initial concentration 60 mg/L. At the optimum condition the removal of malachite green was increased as the initial concentration was increased. The optimum adsorption of malachite green was occurred at pH basic because the pH dependence of dye uptake could be related to functional group of the adsorbent and also to solution chemistry. The dye uptakes were analyzed by using UV-Vis Spectrometer. The result proved that dried water hyacinth is a good adsorbent to remove malachite green from waste water because it is economically feasible and high efficiency of dye removal from dilute solutions and also applicable for industrial.